PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL PADA MATA PELAJARAN SISTEM OPERASI KELAS X MULTIMEDIA SMK NEGERI 6 SURAKARTA TAHUN AJARAN 2015/2016 - Achmad Siddik Fathoni; Basori Basori; AG Tamrin (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2020)
The purpose of this research is to develop media with video technology tutorials that can use in learning of operating system subjects in class X MM 1 6th Vocational High School Surakarta. The method used in this research was Research and Development, in the form of the development of media-based instructional video tutorials and tried out the media in class X Multimedia 1 6th Vocational High School Surakarta. The design was done with a procedure analysis, design, development and workout. The series of product development done by decided the teaching materials and the requirement, design layout and create storyboard, instructional media supporting objects collection, workout of product and revision. Data analysis techniques used in this study was a simple descriptive analysis, which modifying the interval mean of score. These results indicate that ratings matter from content expert who claim that the learning media video tutorial met both criteria once with a percentage of 78,7%. Media expert assessment of the learning media video tutorials with the overall percentage of 87,5% that met both criteria at all. Learning practitioners expert assessment of the learning media video tutorials with the overall percentage of 83,6% that met both criteria. While the responses of students X Multimedia I 6th Vocational High School Surakarta gained the score percentage about 90%, which mean the learning media video tutorials met both criteria at all. It can be concluded that the learning media video tutorials reasonably and can use in learning of operating system subject class X Multimedia I 6th Vocational High School Surakarta.